2014
DOI: 10.1097/fbp.0000000000000018
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent pharmacological modification of cannabinoid-1 and glucagon-like peptide-1 receptor activity affects feeding behavior and body weight in rats fed a free-choice, high-carbohydrate diet

Abstract: To extend preliminary studies on the effects on food intake of the combined use of cannabinoid (CB) 1 and glucagon-like peptide-1 (GLP-1) receptor agonists and antagonists, the effect of these drugs on the feeding behavior in rats maintained on a free-choice, high-carbohydrate diet was investigated over a longer period of time. Rats were fed a standard diet for 3 days and then fed with both the standard and the high-sucrose chow. After 4 days of the high-calorie diet, the following combination treatments were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Several recent studies have suggested a potential interaction between incretin receptors and CB1, particularly with regard to food intake (E. Bojanowska, 2011; Patel et al, 2014; Radziszewska et al, 2014). However, there is a lack of data as to how CB1 would influence the entero-insular axis if both incretin and insulin secretion are impacted by the same receptor system.…”
Section: Introductionmentioning
confidence: 99%
“…Several recent studies have suggested a potential interaction between incretin receptors and CB1, particularly with regard to food intake (E. Bojanowska, 2011; Patel et al, 2014; Radziszewska et al, 2014). However, there is a lack of data as to how CB1 would influence the entero-insular axis if both incretin and insulin secretion are impacted by the same receptor system.…”
Section: Introductionmentioning
confidence: 99%
“…, food-seeking) behavior. On the other hand, the results obtained in our laboratory indicated that AM 251 was not able to reduce selectively food consumption in male Wistar rats that were offered a choice between sweet and normal rat chow [ 82 , 83 ]. This discrepancy may result from different experimental conditions ( e.g.…”
Section: Pharmacological Inhibition Of the Endocannabinoid System Andmentioning
confidence: 99%
“…[ 78 ] and Radziszewska et al . [ 82 ], respectively) as well as from different sensitivity of male and female rats to the CB1 receptor antagonists, an event found originally in mice [ 84 ]. Moreover, AM 251 used at doses comparable to those that specifically decreased sweet food intake in female rats in the aforementioned study by Mathes et al .…”
Section: Pharmacological Inhibition Of the Endocannabinoid System Andmentioning
confidence: 99%
See 2 more Smart Citations